Perbandingan Metode Spektrofotometri dan ICP dalam Penentuan Kesadahan Air - Fahilatul Syukro; Budhi Oktavia (MASALIQ, 2025)
Water is a vital resource whose quality must be ensured for safe consumption and industrial use. One critical parameter in assessing water quality is hardness, typically caused by the presence of calcium (Ca²⁺) and magnesium (Mg²⁺) ions. High levels of hardness can lead to negative effects such as scale formation on equipment, reduced efficiency of boilers and turbines, and potential health issues. This study aims to compare water hardness analysis results obtained using two instruments—Spectrophotometer DR 3900 and Inductively Coupled Plasma (ICP) Perkin Elmer 3800—to identify the strengths and limitations of each method. The research was conducted experimentally using soft water samples collected from boiler piping. Spectrophotometric analysis was based on the Lambert-Beer law by measuring absorbance after adding a complexing reagent, while ICP analysis involved nebulization of filtered and acidified samples using concentrated HNO₃. The results showed that the concentrations of Ca and Mg in the samples were below the hardness threshold (<1 ppm). The highest total hardness measured using the spectrophotometer was 0.524 ppm, while the highest value obtained via ICP was 0.652 ppm. Although both methods produced comparable data, ICP demonstrated superior sensitivity and accuracy, albeit with higher costs and procedural complexity. The study concludes that ICP is recommended for high-sensitivity hardness analysis, whereas the spectrophotometer is more suitable for routine, efficient, and cost-effective testing.